One-step synthesis of Bi2O2Se microstructures for trace oxygen gas sensor application - Bae, Ji Kwon; Cho, Hyeon Ho; Shin, Hojun; Kim, Youngho; Ko, Hyeji; Lee, Seong Joo; Megersa, Daba Deme; Gudena, Gutema Teshome; Chae, Sudong; Cho, In Sun; Yu, Hak Ki (Sensors and Actuators B: Chemical, 2023)
In this study, Bi2O2Se microstructures was successfully synthesized using single-zone Chemical Vapor Deposition (CVD) method, and their performance as an oxygen gas sensor was evaluated. The Bi2O2Se sensor exhibited excellent sensitivity and selectivity to oxygen gas and demonstrated linearity in the range of 10–100 ppm and immune to humidity, confirming its suitability as a trace oxygen sensor. The 1-step synthesis process using single-zone CVD provides a simple and efficient approach for developing high-performance oxygen gas sensors. These results emphasize the potential of Bi2O2Se-based sensors in various gas detection applications.
Keywords: 1-step process; Chemical vapor deposition methods; Large area microstructure; One step synthesis; Oxygen gas; Oxygen gas sensor; Performance; Sensor applications; Single zones; Synthesised; 1-step process; Bi2O2Se; Large area microstructure; Oxygen gas sensor